Rehabilitation assisted by Space technology—A SAHC approach in immobilized patients—A case of stroke - Kourtidou-Papadeli, Chrysoula; Frantzidis, Christos; Machairas, Ilias; Giantsios, Christos; Dermitzakis, Emmanouil; Kantouris, Nikolaos; Konstantinids, Evdokimos; Bamidis, Panagiotis; Vernikos, Joan (Frontiers in Physiology, 2023)
The idea behind the presentation of this case relates to utilizing Space technology in Earth applications with mutual benefit for both patients confined to bed and astronauts. Deconditioning and the progressiveness of the skeletal muscle loss in the absence of adequate gravity stimulus, has been of physiological concern. A robust countermeasure to muscle disuse is still a challenge for both immobilized patients as well as astronauts in long-duration Space missions. Researchers in the Space medicine field concluded that Artificial Gravity (AG) produced by short radius centrifugation on a passive movement therapy device, combined with exercise has been a robust multisystem countermeasure as it reintroduces an acceleration field and gravity load. A Short Arm Human Centrifuge (SAHC) alone or combined with exercise was evaluated as a novel AG device for effective rehabilitation strategy in the case of a stroke patient with disability. The results reveal valuable information on an individualized rehabilitation strategy against physiological deconditioning. A 73-year-old woman was suddenly unable to speak, follow directions, or move her left arm and leg. She could not walk, and self-care tasks required maximal assistance. Her condition was getting worse over the years, although she was receiving conventional rehabilitation treatment. Several consecutive gravity loads from 0.5g to 2.5 g were applied in order to establish the most appropriate rehabilitation g prescription treatment. Intermittent SAHC individualized protocols were applied for 5 months, 3 times a week, 60 treatments in total with significant improvement in her gait, decreased atrophy with less spasticity on the left body side, and ability to walk at least 100 m with a cane. Balance and muscle strength were improved significantly. Cardiovascular parameters improved responding to adaptations to aerobic exercise. Electroencephalography (EEG) showed brain reorganization /plasticity evidenced through functional connectivity alterations and activation in the cortical regions especially of precentral and postcentral gyrus. Stroke immobility-related disability was also improved. These alterations were attributed to the SAHC intervention. This case study provides novel evidence supporting the use of the SAHC as a promising therapeutic strategy in patients with restricted mobility, with application to astronauts with long-term muscle disuse in Space.